2019
DOI: 10.1002/bin.1654
|View full text |Cite
|
Sign up to set email alerts
|

The effect of response interruption and redirection with and without a differential reinforcement of alternative behavior component on stereotypy and appropriate responses

Abstract: Individuals with an Autism Spectrum Disorder (ASD) often engage in repetitive and stereotypic behaviors (American Psychological Association, 2013). Therefore, interventions that reduce stereotypy and potentially increase appropriate responses are of interest in the field of applied behavior analysis. The purpose of this study was to evaluate the isolated and additive effects of response interruption and redirection (RIRD) and differential reinforcement of alternative behavior (DRA) on both stereotypy and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…We explained how instructions and rewards should be efficiently applied (e.g., brief, clear, short and consistent instructions, provided when the target response was not being produced; reward applied immediately after the target response). Undesirable behaviors had to be gently and briefly interrupted, and the child immediately prompted to provide the target response (Cividini-Motta et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…We explained how instructions and rewards should be efficiently applied (e.g., brief, clear, short and consistent instructions, provided when the target response was not being produced; reward applied immediately after the target response). Undesirable behaviors had to be gently and briefly interrupted, and the child immediately prompted to provide the target response (Cividini-Motta et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of implementing the intervention within the natural environment on appropriate vocalizations may have impacted the results; however, this was not controlled for nor directly assessed. Whereas previous research does demonstrate an increase in appropriate vocalizations during RIRD, a recent study supports the current findings where no significant increase was observed (Cividini‐Motta et al, ). These results support the importance of programming for language acquisition when designing an intervention to decrease stereotypic behavior in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This was the finding for some participants whose stereotypy occurred at baseline levels when data were reported and included from implementation intervals (Wunderlich & Vollmer, ). However, evidence for vocal stereotypy suppression when interval data are included was demonstrated by Cividini‐Motta et al (). This will likely be an area for further investigation and comparison to ensure accurate data reporting within the future research of RIRD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ahearn, Clark, MacDonald, and Chung () successfully decreased vocal stereotypy and increased appropriate communication using RIRD for three children with autism; additionally, follow‐up probes suggested that these treatment effects persisted in the children's natural environment. Preliminary research suggests RIRD may effectively decrease stereotypy either when used in isolation or when combined with a differential reinforcement of alternative behavior (DRA) contingency for appropriate responding (Cividini‐Motta, Garcia, Livingston, & MacNaul, ). That is, research has investigated alternative procedures for decreasing stereotypic behavior via differential reinforcement or contingent access to stereotypy (Potter, Hanley, Augustine, Clay, & Phelps, ).…”
Section: Introductionmentioning
confidence: 99%